Justice alternatives - Carlen, Pat; França, Leandro Ayres (Routledge, 2020)
Justice is one of the most debated and reinterpreted of concepts within the fields of law, criminology and criminal justice. Bringing together 35 leading thinkers, analysts and campaigners from around the world, this collection presents a range of on-going struggles for justice from abolitionist, transitional, transformative, indigenous, green and restorative perspectives.